2022
DOI: 10.1063/5.0122275
|View full text |Cite
|
Sign up to set email alerts
|

The electrostatic potential inside and around α-lactalbumin: Fluctuations and mean-field models

Abstract: The electrostatic potential (EP) generated by the protein α-lactoalbumin in the presence of added salt is computed as a thermal average at a given point in the space. With this aim constant pH Monte Carlo (MC) simulations are performed within the primitive model, namely, the solvent is treated as a continuum dielectric. The study of the thermal and spatial fluctuations of the EP reveals that they are remarkably high inside the protein. The calculations indicate that fluctuations inside the protein are mainly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The presence of small ions reduces the repulsion between negative charges, allowing an increase in the deprotonation of acidic groups. 36 Moreover, our MC simulation results showed that the isoelectric point was not affected by the different salt concentrations studied, pI = 4.9 AE 0.1. Even though our MC results deviate from the experimental values, they are within the range of other theoretical models.…”
Section: Isolated A-lactalbuminmentioning
confidence: 73%
See 4 more Smart Citations
“…The presence of small ions reduces the repulsion between negative charges, allowing an increase in the deprotonation of acidic groups. 36 Moreover, our MC simulation results showed that the isoelectric point was not affected by the different salt concentrations studied, pI = 4.9 AE 0.1. Even though our MC results deviate from the experimental values, they are within the range of other theoretical models.…”
Section: Isolated A-lactalbuminmentioning
confidence: 73%
“…The decline in the surface electrostatic potential profiles does not show linearity with the pH; instead, it was demonstrated that its linearity correlates with the net charge of the protein. 36 Previously, we observed that at the same pH value, the average charge increased with the salt concentration. So these electrostatic potential jumps are dependent on the salt concentration in the medium and its shielding effect.…”
Section: Isolated A-lactalbuminmentioning
confidence: 83%
See 3 more Smart Citations